Effort provision as a reference point in risk decision-making - Leong, Carissa Jun Wei (2019)
This paper presents evidence on the effect of effort provision on the risk attitude of individuals through the mechanism of reference point. Effort is found to be perceived as part of people’s decision costs and is also capable of shaping their expectations, which are fundamental in the formation of reference points. We hypothesize that greater effort involved would lead to more risk-loving behaviors by raising subjects’ expectations and reference points, thus propelling them to take on more risk to gain a higher reward. In this study, we manipulate the effort level and elicit the effect on individuals’ risk preferences through investment decision-making. The experiment is programmed with the z-Tree software and 186 undergraduates were randomly allocated to four treatment groups which required different effort levels to obtain the same investment amount for the investment decision task. We observe that subjects who have exerted greater effort indeed exhibited a higher risk-taking attitude, which is consistent with our hypothesis. This result illustrates that these decision costs appear to have a significant effect on the behaviors of subjects in monetary investment decision task.